'Real Gs and pastors in the church': hip-hop esthetics in the rap music video productions of the Evangelical Lutheran Church of Finland. Issue 3 (3rd July 2022) - Järvenpää, Tuomas
ABSTRACT: Previous studies of Christianity and hip-hop have mainly focused on the US and African American cultural context, and on evangelical minorities in different anglophone contexts. The current study offers a novel perspective on the study of Christianity and hip-hop by presenting an audiovisual close reading of two rap music videos – Kaunis Jeesus and Hoosianna – that were commissioned by a Nordic mainline church institution, the Finnish Evangelical Lutheran Church. The paper identifies two articulations of hip-hop esthetics in these audiovisual productions. The first articulation follows the common evangelical approach to popular music and is marked by the absence of many of the esthetic traits of secular hip-hop culture while the second articulation embraces the stylistic practices of hip-hop in order to communicate that the church is a culturally inclusive institution and to counter the exclusivist ideologies of the nationalist-populist political movements.